Treatment Strategy With Gene Editing for Late-Onset Retinal Degeneration Caused by a Founder Variant in C1QTNF5 - Li, Randa T. H.; Roman, Alejandro J.; Sumaroka, Alexander; Stanton, Chloe M.; Swider, Malgorzata; Garafalo, Alexandra V.; Heon, Elise; Vincent, Ajoy; Wright, Alan F.; Megaw, Roly; Aleman, Tomas S.; Browning, Andrew C.; et al. (Investigative ophthalmology & visual science, 2023)
Genome editing is an emerging group of technologies with the potential to ameliorate dominant, monogenic human diseases such as late-onset retinal degeneration (L-ORD). The goal of this study was to identify disease stages and retinal locations optimal for evaluating the efficacy of a future genome editing trial. Twenty five L-ORD patients (age range, 33-77 years; median age, 59 years) harboring the founder variant S163R in C1QTNF5 were enrolled from three centers in the United Kingdom and United States. Patients were examined with widefield optical coherence tomography (OCT) and chromatic perimetry under dark-adapted and light-adapted conditions to derive phenomaps of retinal disease. Results were analyzed with a model of a shared natural history of a single delayed exponential across all subjects and all retinal locations. Critical age for the initiation of photoreceptor loss ranged from 48 years at the temporal paramacular retina to 74 years at the inferior midperipheral retina. Subretinal deposits (sRET-Ds) became more prevalent as critical age was approached. Subretinal pigment epithelial deposits (sRPE-Ds) were detectable in the youngest patients showing no other structural or functional abnormalities at the retina. The sRPE-D thickness continuously increased, reaching 25 µm in the extrafoveal retina and 19 µm in the fovea at critical age. Loss of light sensitivity preceded shortening of outer segments and loss of photoreceptors by more than a decade. Retinal regions providing an ideal treatment window exist across all severity stages of L-ORD.